PENGARUH PEMBERIAN ASAP CAIR TERHADAP PERTUMBUHAN RUMPUT RAJA (Pennisetum purpureophoides) - Muhakka, -; Napoleon, A.; Isti’adah, Hidayatul (Pastura; Vol 3 No 1DO - 10.24843/Pastura.2013.v03.i01.p08)
This research aimed to determine the effect of liquid smoke and to determine the optimal dose of liquid smoke to the growth of king grass (Pennisetum purpureophoides). The research was conducted at the experimental farm Livestock and Laboratory of Chemistry, Biology and Soil Fertility, Soil Department, Faculty of Agriculture, SriwijayaUniversity, for 4 months that was from November until February 2013. This research used randomized block design (RBD) with 5 treatments and each treatment consisted of 3 block as replicates. The treatment used was liquid smoke, with doses A0=0% liquid smoke, A1=2% liquid smoke, A2=4% liquid smoke, A3=6% liquid smoke and A4=8% liquid smoke. The parameters observed were height plant, number of tillers and number of leaves. The results showed that giving liquid smoke on the best high of king grass on treatment A2 (4% liquid smoke) was 382.50 cm and the number of tillers and leaves found on the A1 (2% liquid smoke) was 13.67 rods and 140,42 strands. The conclusions that giving liquid smoke have not significant effecton the growth of the king grass, but seen from the growth, number of tillers and number of leaves, the optimal giving liquid smoke at a dose 2%.
Keywords: liquid smoke, growth and king grass.